2012
DOI: 10.5604/15093492.1002257
|View full text |Cite
|
Sign up to set email alerts
|

Influence of various laser therapy methods on knee joint pain and function in patients with knee osteoarthritis

Abstract: One-wave laser irradiation at a dose of 8 J per point and two-wave laser irradiation with doses of 12.4 J and 6.6 J per point significantly improved knee joint function and relieved knee pain in patients with osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…The effectiveness of MLS laser therapy has also been observed in knee osteoarthritis [18]. In placebo-controlled double-blind intervention study, a reduced frequency and intensity of attacks in patients with primary Raynaud’s phenomenon after 3 weeks of low-level laser therapy (LLLT) has been demonstrated; however, the mechanisms of these effects remain unclear [16].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of MLS laser therapy has also been observed in knee osteoarthritis [18]. In placebo-controlled double-blind intervention study, a reduced frequency and intensity of attacks in patients with primary Raynaud’s phenomenon after 3 weeks of low-level laser therapy (LLLT) has been demonstrated; however, the mechanisms of these effects remain unclear [16].…”
Section: Discussionmentioning
confidence: 99%
“…This may be partly due to conflicting results of two recently published systematic reviews on the current topic 8 17. The conflicting results may arise from omission of relevant trials8 17–23 and unresolved LLLT dose-related issues. Only Huang et al 17 conducted a LLLT dose–response relationship investigation in KOA, that is, by subgrouping the trials by laser dose, but they did not consider that World Association for Laser Therapy (WALT) recommends applying four times the laser dose with continuous irradiation compared to superpulsed irradiation 22 24–26.…”
Section: Introductionmentioning
confidence: 99%
“…Low level laser therapy stimulates microcirculation, reduces pain and the inflammatory process, and reduces the frequency and intensity of attacks in patients with primary and secondary RP [26][27][28][29]. Regarding the clinical efficacy of MLS laser therapy, only a few reports may be considered as evidence in the treatment of patients with primary and secondary RP [14,26].…”
Section: Discussionmentioning
confidence: 99%
“…In randomized placebo-controlled trials after 3 weeks of infrared thermography, the authors observed a decrease in the number of attacks, the duration of a single attack, and intensity [27]. The beneficial effect of MLS treatment was observed in patients with knee osteoarthritis [28]. MLS laser therapy allowed modulating the inflammatory response in an experimental model of collageninduced rheumatoid arthritis, and the therapy is effective in both the early and the late progression stage of collagen-induced rheumatoid arthritis [29].…”
Section: Discussionmentioning
confidence: 99%